Analisis Faktor Penyebab Keterlambatan Pelaksanaan Proyek Pembangunan Gedung Apartemen 31 Sudirman Suites Makassar - Sonaigh Bano Ongan; Josefine Ernestine Latupeirissa; Herby Calvin Pascal Tiyouw (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
Problems occur in construction projects that arise from inconsistencies in plans that have been made with actual facts, so that the impact that often occurs is a matter of project implementation time. The construction project of the 31 Sudirman Suites Apartment Building, located in the city of Makassar, South Sulawesi, will be underway starting March 24, 2020 and the contract completion plan is July 2021 with an initial schedule of 16 months. In the process of structural work has occurred, the project (project schedule delay) is approximately 10 months drawn from July 2020 to April 2021, where the final condition at the review stage of the S-curve data is known that the planned development (planned progress) is 82.695% of the actual progress (actual progress) of 47.449% so there was a project incidence of 35.246%, namely the difference between the actual / realization time schedule and the initial plan. This study aims to determine the factors causing the implementation of the 31 Sudirman Suites Makassar Apartment building project. The method used in this research is by means of a questionnaire to the relevant agencies as many as 20 responsibilities. Data analysis used descriptive statistics, validation and reliability tests, Relative Rank Index (RRI). From the research results, the dominant factor that caused the implementation of the 31 Sudirman Suites Apartment Building construction project was unexpected events (force majeure), such as the corona virus pandemic (COVID 19) with an RRI value of 0.892.